Trusted Execution Environments: Applications and Organizational Challenges - Geppert, Tim; Deml, Stefan; Sturzenegger, David; Ebert, Nico (Frontiers in Computer Science, 2022)
A lack of trust in the providers is still a major barrier to cloud computing adoption – especially when sensitive data is involved. While current privacy-enhancing technologies such as homomorphic encryption can increase security but come with a considerable performance overhead. As an alternative Trusted Executing Environments (TEE) provide trust guarantees for code execution in the cloud similar to transport layer security for data transport or advanced encryption standard algorithms for data storage. Cloud infrastructure providers like Amazon, Google, and Microsoft introduced TEEs as part of their infrastructure offerings. This review will shed light on the different technological options of TEEs as well as give insight into organizational issues regarding their usage.